The Impact of Social-media Celebrity on Buying Behavior of Retailer Customers in Riyadh, KSA - A. A. Al-Nsour, Iyad (Jordan Journal of Business Administration, 2023)
This study aimed to measure the impact of celebrity endorsement on the buying behavior of retailer customers in Riyadh. The study population consists of all buyers of hyper-stores in Riyadh. The unit of analysis was the Saudis and non-Saudis who are employed in the government and private sectors in Riyadh. The estimates showed that the size of the population reached 3.87 million people in 2019. The stratified-sample technique was used and the recommended sample size reached 387 buyers. The results of structural equation modeling (SEM) showed a statistically significant impact of celebrity on the purchasing behavior of retailer customers in Riyadh. Finally, the study presented several recommendations and marketing implications to enhance the role of celebrity in purchasing decisions.